Potencial de Danos Econômicos Face à Erosão Costeira, Relativo às Praias da Costa do Descobrimento – Litoral Sul do Estado da Bahia - SILVA, IRACEMA REIMÃO; PINTO BITENCOURT, ABÍLIO CARLOS DA SILVA; DOMINGUEZ, JOSÉ MARIA LANDIM; DE MELLO E SILVA, SYLVIO BANDEIRA (Pesquisas em Geociências, 2007)
<!– .p text-align: justify; –> An evaluation of the potential economic damage to the Discovery Coast beaches, in southern Bahia, due to their susceptibility to erosion and urbanization level, indicates that 60% beaches have a low level of damage, 30% have a medium level and 10% are already highly damaged. These beaches with the highest level of damage are the ones heavily urbanized and exposed to erosion, or are located close to river’s mouth. The data obtained from this work will certainly be of a great value for the effectiveness of planning and managing the Discovery Coast beaches such as, for example, showing to the decision-makers the need for investing into the tourism development, coupled with questions related to the land use.